1995
DOI: 10.1007/bf02634569
|View full text |Cite
|
Sign up to set email alerts
|

Matrix proteins associated with bone calcification are present in human vascular smooth muscle cells grownin vitro

Abstract: Atherosclerotic lesions are composed of cellular elements that have migrated from the vessel lumen and wall to form the cellular component of the developing plaque. The cellular elements are influenced by various growth-regulatory molecules, cytokines, chemoattractants, and vasoregulatory molecules that regulate the synthesis of the extracellular matrix composing the plaque. Because vascular smooth muscle cells (VSMC) constitute the major cellular elements of the atherosclerotic plaque and are thought to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Monocyte-macrophages and smooth muscle cells synthesize osteopontin (18,22,(40)(41)(42)(43)(44)(45)(46), matrix Gla protein (43,46) and osteonectin (43) in cell culture, atherosclerotic plaques (41,42,45), or restenotic neointima (22,42,47). Vascular pericyte-like cells (23,48), monocytes (49), and endothelial cells (45) also express osteopontin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte-macrophages and smooth muscle cells synthesize osteopontin (18,22,(40)(41)(42)(43)(44)(45)(46), matrix Gla protein (43,46) and osteonectin (43) in cell culture, atherosclerotic plaques (41,42,45), or restenotic neointima (22,42,47). Vascular pericyte-like cells (23,48), monocytes (49), and endothelial cells (45) also express osteopontin.…”
Section: Discussionmentioning
confidence: 99%
“…Such a concept is in keeping with the idea that the mineralization of extraskeletal tissues passively termed "dystrophic mineralization" is, in fact, a coordinated cell-mediated process. There is emerging evidence that other related reparative processes such as atherosclerotic calcification and coronary restenosis also involve cell-mediated, coordinated matrix protein expression (18,(22)(23)(24)(43)(44)(45)(46)(47)(48). Studies in different species have shown that both mRNA and protein for osteopontin are closely associated with osteoblasts, osteocytes, osteoclasts, smooth muscle cells, endothelial cells, foam cells, macrophages, and pericyte-like cells around zones of calcification (18,19,(22)(23)(24)50).…”
Section: Discussionmentioning
confidence: 99%
“…ON is detected in cultured SMCs (Severson et al 1995) and is strongly expressed in young but not in healthy adult vessel walls. However, a few ON-expressing cells were scattered throughout the atherosclerosic lesions in humans (Hirota et al 1993).…”
mentioning
confidence: 94%
“…Due to the presence of collagenous and noncollagenous proteins associated with bone mineralization in vascular smooth muscle cells (SMCs), vascular SMCs within developing atherosclerotic plaques play an important role in the deposition of extracellular matrix, resulting in vascular calcification (8). During vascular calcification, various vascular cells, including vascular SMCs, pericytes, fibroblasts, and macrophages, are transformed into osteoblast-like phenotypes, exhibit increased alkaline phosphatase (ALP) activity, and matrix vesicle formation, and show significant expressions of the genes for bone morphogenetic protein 2 (BMP2) and bone matrix proteins such as osteocalcin and osteopontin (9,10).…”
Section: Introductionmentioning
confidence: 99%